Embedding Check sums LSB with CCD Methods for Detecting Changes in Digital images - -, Vastav; -, Rajat (Journal of Advanced Research in Information Technology, Systems and Management, 2024)
The goal of this paper is to design a watermarking scheme capable of distinguishing visible but non-malicious changes due to common image processing operations from malicious changes, such as feature adding/replacement. We start with an overview of watermarking techniques for detection of tampering in digital images and discuss their limitations. A new technique that inserts robust watermarks into small disjoint blocks is proposed. The technique can be implemented with small memory and computational requirements, which makes it potentially useful for hardware implementation in digital cameras. This paper further extends our previous effort